PENGGUNAAN AKAD MURABAHAH DALAM PEMBIAYAAN KEPEMILIKAN RUMAH DENGAN SISTEM MUSYARAKAH - GATTA ANANDYA, AURELLIA (Berkala Ilmiah Mahasiswa Akuntansi)
All human beings have three basic needs, food, clothing and shelter (house). Among these, the board need the highest cost. Many people are willing to make loans to the Bank to take the credit in the purchase of a home. Murabahah contract seems to fit the needs of the consumer lending and borrowing related issues between the customer and the Bank. Murabahah contract is an agreement which the goods are sold at cost plus a profit that has been agreed between the Bank shall disclose the acquisition price of such goods to the customer. But the installment of the loan using a system of installment payments Musyarakah, where the loan principal plus the margin of financing a system of Musyarakah financing installments of which the share of profits and share losses according to the agreement ini accordance with the portion of capital contribution of each party.